Construction of Maqashid Syariah according to Jasser Auda in the Perspective of Islamic Economic Law: Theoretical Analysis and Implementation - Alamsyah, Tahwin; Musyahid, Ahmad; Sultan, Lomba (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2025)
Maqashid Syariah refers to the goals that Islamic law seeks to achieve in ensuring the well-being of humanity in social, political, and economic aspects. One contemporary thinker, Jasser Auda, has made significant contributions to the theory of Maqashid Syariah by emphasizing the importance of flexibility and relevance of its principles in the context of modern times, particularly in the field of Islamic economics. This study aims to analyze the implementation of Auda's Maqashid Syariah theory in the Islamic economic system using a qualitative approach through a literature review. The method used is descriptive analysis to explore the application of Maqashid Syariah principles in Islamic economics, such as economic justice, economic empowerment, human rights protection, and equitable wealth distribution. The results show that the application of Auda's principles can help create an inclusive, just, and sustainable economic system, focusing on the well-being of humanity. The discussion highlights the importance of adjusting Islamic law to contemporary social and economic dynamics, as well as the implementation of economic policies that support the well-being of society as a whole. The conclusion of this study is that Auda's theory is relevant in formulating Islamic economic law that addresses social inequality and economic injustice.